The Transformation of Alkyl- and Aryl-Sodium Reagents with Simple Amides for the Direct Synthesis of Ketones - Knupe-Wolfgang, Paula; Hilt, Gerhard (Synthesis, 2025)
The transformation of alkyl and aryl sodium reagents with N-alkyl amides is described. The reaction sequence is initiated by an alkyl sodium reagent, which is generated in a flow reactor. The alkyl sodium reagent is either directly reacted with N-alkyl amides or used for the reaction with alkyl-substituted or alkoxy-substituted arenes to generate secondary sodium reagents which were then reacted with the amides to afford the desired ketones in moderate to good yields.
Keywords: Alkyl sodium; Alkylation; Amides; Ketones; Sodiation; Transsodiation